Gross Morphological And Biometrical Studies On Thyroid Gland In Bakerwali Goat (Capra Hircus) (Applied Biological Research, 2018)
The present study was conducted on 36 samples of thyroid glands of Bakerwali  goat, divided into 3 groups based on the age of animals viz., prepubertal (5 years). Thyroid gland was located on  the dorsolateral aspect of trachea. The gland was bilobed, reddish brown in  colour, elongated and elliptical in outline. The right lobe of gland extended from  posterior extremity of larynx to 5th tracheal ring, while left lobe extended from  extremity of larynx to 7th tracheal ring. The two lobes were connected  by isthmus around the ventral aspect of trachea and position varied between 5th and 6th tracheal ring. The mean length of left lobe was larger than right lobe in  all the age groups. The biometrical parameters increased with the advancement  of age. The isthmus connected the caudal poles of two lobes of gland. The  isthmus was glandular in young animals and was becoming fibrous in older  ones.
Keywords: Bakerwali goat; isthmus; larynx; thyroid; tracheal ring